Сказка о рыбаке и рыбке - Пушкин Александр Сергеевич (Серия "Стихи и сказки малышам", 2014)
Экземпляры: ДО мл.аб. (2023) / Инвентарный номер: 59206 / Цена: / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: П 91 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1